OPTIMALISASI PERAN GURU TK DALAM INTERVENSI GANGGUAN EMOSI DAN PERILAKU ANAK USIA DINI - Shoofii Syammari; Nina Permata Sari; Noor Ainah; Asih Nor Zahidah; Nurrofifah, Hani (LP2M IAIN Sultan Amai Gorontalo, 2025)
ABSTRACT This study aims to analyze the optimization of kindergarten teachers’ roles in intervening with emotional and behavioral disorders in early childhood. The research focuses on four indicators, namely teachers’ understanding and knowledge of children’s emotional-behavioral development, their skills in implementing interventions, attitudes of concern toward children’s conditions, and collaboration with parents as well as intervention evaluation. The study employed a quantitative approach with a survey design. The sample consisted of 30 kindergarten teachers from the Sa’adah Foundation in Martapura, selected using purposive sampling. Data were collected through a rating-scale questionnaire and analyzed using descriptive statistics, categorized into low, medium, high, and very high levels. The findings indicate that the role of kindergarten teachers has not been optimized in most indicators. Teachers’ understanding and knowledge (mean score 8.65), intervention skills (12.94), and collaboration with parents and evaluation (10.2) were categorized as low. Meanwhile, teachers’ attitudes and concern for children (21.28) were categorized as high. This reveals a gap between teachers’ emotional concern and their conceptual as well as technical competence in carrying out interventions. Therefore, optimizing the role of kindergarten teachers requires capacity strengthening through training, mentoring, and continuous collaboration with parents and professionals. This study is expected to contribute to the development of socio-emotional intervention studies in young children and deliver practical benefits for teachers, schools, parents, and decision-makers in designing effective, responsive, and inclusive educational strategies.